PERAN VARIASI PRODUK, LOKASI DAN STORE ATMOSPHERE DALAM MENCIPTAKAN LOYALITAS KONSUMEN - Hapsari, Dini Rahma Putri; Octavia, Ayu Nurafni (STIE PENA, 2025)
The purpose of this study was to analyze the effect of product variation, location and Store Atmosphere on consumer loyalty at Indomaret Point Majapahit in Semarang City. The population of this study were consumers who made purchases at Indomaret Point Majapahit, Jl. Majapahit No. 234 E, Semarang. The number of samples taken was 96 respondents, the type of data used was primary data. The data collection method used a questionnaire. The analysis technique used was multiple regression analysis and the tests carried out were hypothesis testing, F-test and coefficient of determination. The tool used to conduct data analysis was SPSS version 26. The results of the analysis showed that Product Variation had a positive and significant effect on consumer loyalty, Location had a positive and significant effect on consumer loyalty, Store Atmosphere had a positive and significant effect on consumer loyalty. Simultaneously, Product Variation, Location and Store Atmosphere had a joint effect on consumer loyalty